A 1.9 µm femtosecond fiber laser using a 3D printed, all-fiberized graphene/polylactic-acid saturable absorber. (20th June 2019) - Woo, G; Lee, J; Lee, J H
Abstract: We experimentally demonstrate the fabrication of an all-fiberized saturable absorber (SA) suitable for ultrafast mode-locking of a fiber laser operating in the 1.9 µ m wavelength region, using three-dimensional (3D) printing technology. An all-fiberized SA was fabricated by 3D-printing a low-cost composite filament of graphene and polylactic-acid (PLA) onto a side-polished fiber. The measured modulation depths of the fabricated SA are ~5% and ~3.5% at 1.9 µ m for the transverse electric and transverse magnetic modes, respectively. Using the SA within a thulium (Tm)-holmium-codoped fiber-based ring cavity, it is shown that mode-locked pulses with a temporal width of ~924 fs are readily obtainable. It is believed that this experimental demonstration reaffirms the potential of the graphene/PLA filament-based 3D printing technique for the fabrication of practical wideband SAs.